Syndemic Synergy of HPV, HIV, and HSV-2 for Oncogenic HPV Replication in Female Sex Workers - Jonathan Muwonga Tukisadila; Ralph-Sydney Mboumba Bouassa; Serge Tonen-Wolyec; Hugues Loemba; Jeremie Muwonga; Laurent Belec (Tropical Medicine and Infectious Disease)
Background: Female sex workers (FSWs) in sub-Saharan Africa bear a disproportionate burden of sexually transmitted infections, including HIV, high-risk HPV (HR-HPV), and herpes simplex virus type 2 (HSV-2). This study evaluated possible association between HR-HPV, HIV, and HSV-2 among FSWs in the Democratic Republic of the Congo. Methods: A cross-sectional study was conducted among 432 FSWs (mean age, 28.1 years) recruited via respondent-driven sampling. Genital self-sampling using the V-Veil UP2™ device was performed, followed by HPV genotyping and quantification by multiplex PCR, and HSV-2 DNA detection by PCR. Results: Among 415 participants, HR-HPV prevalence was 36.9%, with HPV-52 (14.9%), HPV-58 (10.1%), and HPV-16 (6.5%) as leading genotypes. Overall, 89% of HR-HPV-positive women harbored genotypes covered by Gardasil-9®. Co-infection with HIV and HSV-2 significantly increased HPV prevalence, genotype diversity, and viral load. Notably, HSV-2 positivity was the sole independent predictor of elevated replication of HR-HPV (p < 0.001), vaccine HR-HPV (p < 0.001), and non-vaccine HR-HPV (p < 0.021). Conclusions: FSWs exhibit a high burden of HR-HPV, shaped by co-infections with HIV and HSV-2. HSV-2 independently drives HR-HPV replication, highlighting its role in HPV persistence and cervical cancer risk. Integrated HSV-2 detection and Gardasil-9® vaccination should be prioritized in cervical cancer elimination strategies targeting high-risk populations in sub-Saharan Africa.